A Pathogenic Variant p.Phe177Val in PSEN1 Causes Early-Onset Alzheimer’s Disease in a Chinese Family - Jiang, Bin; Bi, Min; Li, Jun; Liu, Qi; Xiao, Nai-An; Fang, Jie; Shi, Man-Yi; Yu, Zi-Wen; Ma, Qi-Lin; Tong, Sui-Jun; Zheng, Kun-Mu (Frontiers in Genetics, 2020)
Familial Alzheimer’s disease (FAD) present as a positive family history of cognitive decline, with early onset and an autosomal dominant inheritance pattern. FAD is mainly caused by the mutations in the genes encoding for amyloid precursor protein (APP), presenilin-1 (PSEN1), and presenilin-2 (PSEN2). In the present study, we identified a variant (c.529T>G, p.Phe177Val) in PSEN1 across three generations in a Chinese family with FAD using whole-exome sequencing. The mean age of onset was 39 years (range: 37 to 40 years) in this family. In cell transfection studies, the mutant PSEN1 protein carrying p.Phe177Val increased both the production of Aβ42 and the ratio of Aβ42 over Aβ40, as compared to wild-type PSEN1. Our results conﬁrm the pathogenicity of PSEN1 p.Phe177Val variant in FAD and broaden the clinical phenotype spectrum of FAD patients with PSEN1 p.Phe177Val variant.